Non-canonical WNT signalling in cardiovascular disease: mechanisms and therapeutic implications - Akoumianakis, I; Polkinghorne, M; Antoniades, C (Springer Nature, 2022)
WNT signalling comprises a diverse spectrum of receptor-mediated pathways activated by a large family of WNT ligands and influencing fundamental biological processes. WNT signalling includes the β-catenin canonical pathway and the non-canonical pathways, namely the planar cell polarity and the calcium-dependent pathways. Advances over the past decade have linked non-canonical WNT signalling with key mechanisms of atherosclerosis, including oxidative stress, endothelial dysfunction, macrophage activation and vascular smooth muscle cell phenotype regulation. In addition, non-canonical WNT signalling is involved in crucial aspects of myocardial biology, from fibrosis to hypertrophy and oxidative stress. Importantly, non-canonical WNT signalling activation has complex effects in adipose tissue in the context of obesity, thereby potentially linking metabolic and vascular diseases. Tissue-specific targeting of non-canonical WNT signalling might be associated with substantial risks of off-target tumorigenesis, challenging its therapeutic potential. However, novel technologies, such as monoclonal antibodies, recombinant decoy receptors, tissue-specific gene silencing with small interfering RNAs and gene editing with CRISPR–Cas9, might enable more efficient therapeutic targeting of WNT signalling in the cardiovascular system. In this Review, we summarize the components of non-canonical WNT signalling, their links with the main mechanisms of atherosclerosis, heart failure and arrhythmias, and the rationale for targeting individual components of non-canonical WNT signalling for the treatment of cardiovascular disease.